Exploring the experiences of minoritised groups at life sciences conferences in the UK: new perspectives and actions to improve inclusivity in the sector [version 3; peer review: 1 approved, 2 approved with reservations] - Tinu Cornish; Hayley Clissold; Ashlee Christoffersen; Janice Prentice; Kathlyn Wilson; Victor Penda; Ireena Dutta; Julian C. Rayner; Michelle Bishop; Saher Ahmed; Treasa Creavin (Wellcome Open Research)
Attending and participating in scientific research meetings and conferences is a key mechanism for researchers to share information and knowledge, build networks, and establish relationships and collaborations to support career development. In the UK, researchers from minoritised or underrepresented groups may have a different experience at a conference than their peers. As a high profile provider of genomics-focussed life science conferences, Wellcome Connecting Science is committed to ensuring that our events are as inclusive as possible. Here we summarise the findings of a project to explore the experiences of minoritised groups, with a focus on race and ethnicity, and discuss how we are seeking to improve access and inclusion at our conferences.